Autologous tolerogenic dendritic cells for rheumatoid and inflammatory arthritis. Issue 1 (26th April 2016) - Bell, G M; Anderson, A E; Diboll, J; Reece, R; Eltherington, O; Harry, R A; Fouweather, T; MacDonald, C; Chadwick, T; McColl, E; Dunn, J; Dickinson, A M; et al.
Abstract : Objectives: To assess the safety of intra-articular (IA) autologous tolerogenic dendritic cells (tolDC) in patients with inflammatory arthritis and an inflamed knee; to assess the feasibility and acceptability of the approach and to assess potential effects on local and systemic disease activities. Methods: An unblinded, randomised, controlled, dose escalation Phase I trial. TolDC were differentiated from CD14+ monocytes and loaded with autologous synovial fluid as a source of autoantigens. Cohorts of three participants received 1×10 6, 3×10 6 or 10×10 6 tolDC arthroscopically following saline irrigation of an inflamed (target) knee. Control participants received saline irrigation only. Primary outcome was flare of disease in the target knee within 5 days of treatment. Feasibility was assessed by successful tolDC manufacture and acceptability via patient questionnaire. Potential effects on disease activity were assessed by arthroscopic synovitis score, disease activity score (DAS)28 and Health Assessment Questionnaire (HAQ). Immunomodulatory effects were sought in peripheral blood. Results: There were no target knee flares within 5 days of treatment. At day 14, arthroscopic synovitis was present in all participants except for one who received 10×10 6 tolDC; a further participant in this cohort declined day 14 arthroscopy because symptoms had remitted; both remained stable throughout 91 days of observation. There were no trends in DAS28 or HAQ score or consistent immunomodulatory effects in peripheral blood. 9 of 10 manufactured products met quality control release criteria; acceptability of the protocol by participants was high. Conclusion: IA tolDC therapy appears safe, feasible and acceptable. Knee symptoms stabilised in two patients who received 10×10 6 tolDC but no systemic clinical or immunomodulatory effects were detectable. Trial registration number: NCT01352858.